Kaifiyyah Sholat - Alya Sukmasyariah; Faniska Aline Alfajri; Mikaila Nur Tsaqifa Al Ma’arif; Rida Sofia; Nur Wakhid (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
Prayer is a primary form of worship in Islam, with detailed procedures (kaifiyyah) established based on the Qur'an and Hadith. This study aims to examine the concept of kaifiyyah of prayer, encompassing its definition, legal basis, and practical implementation in daily life. The method used is a literature study by analyzing various classical and contemporary literary sources. The results show that kaifiyyah of prayer encompasses not only physical movements but also aspects of recitation, reverence, and understanding of the meaning contained therein. A correct understanding of kaifiyyah of prayer is crucial for worship to be carried out in accordance with Islamic law and to have optimal spiritual value. Therefore, this study is expected to increase awareness among Muslims in performing prayer correctly and perfectly.